Response of pepper plants (Capsicum annum L.) on soil amendment by inorganic and organic compounds of arsenic - Száková, Jirina; Tlustos, Pavel; Goessler, Walter; Pavlíková, Daniela; Schmeisser, Ernst (Archives of environmental contamination and toxicology, 2007)
The influence of soil contamination by inorganic and organic arsenic compounds on uptake, accumulation, and transformation of arsenic in pepper (Capsicum annum L.) was investigated in greenhouse pot experiments under controlled conditions. Pepper plants were cultivated in substrate amended by aqueous solutions of arsenite, arsenate, methylarsonic acid (MA), and dimethylarsinic acid (DMA) applied individually into cultivation substrate at concentrations of 15 mg As per kg of substrate. The plant availability of the arsenicals increased in the order arsenite = arsenate < MA < DMA. The highest arsenic concentrations were found in roots followed by stems, leaves, and fruits regardless of arsenic compound applied. In the control samples of pepper fruits, As(III), As(V), and DMA were present (25%, 37%, and 39% of the water-extractable arsenic). In control stems + leaves and roots, As(V) was the major compound (63% and 53% in a phosphate buffer extract) followed by As(III) representing 33% and 42%. Additionally, low concentrations (not exceeding 5%) of DMA and MA were detected as well. In all the soils analyzed after the first harvest of pepper fruits, arsenate was the dominating compound followed by arsenite. Methylarsonic acid, methylarsonous acid, and DMA were present at varying concentrations depending on the individual soil treatments. In the treated plants, the arsenic compounds in plant tissues reflected predominantly the extractable portions of arsenic compounds present in soil after amendment, and this pattern was more significant in the first part of vegetation period. The results confirmed the ability of generative parts of plants to accumulate preferably organic arsenic compounds, whereas in the roots and aboveground biomass, mainly inorganic arsenic species are present. Evidently, the source of soil arsenic contamination affects significantly the extractable portions of arsenic compounds in soil and subsequently the distribution of arsenic compounds within the plants.
Keywords: hmotnostní spektrometrie s elektrosprejovou ionizací; kyselina kakodylová; arsenitany; arseničnany; arsenikové přípravky; Plant Structures; Cacodylic Acid; Chromatography, High Pressure Liquid; Arsenites; Arsenicals; Capsicum; stavba rostlin; látky znečišťující půdu; vysokoúčinná kapalinová chromatografie; Arsenates; arsen; Spectrometry, Mass, Electrospray Ionization; Soil Pollutants; Arsenic